Pengelompokan Kecamatan di Provinsi Bali Berdasarkan Indeks Desa Membangun (IDM) Tahun 2022 dengan Analisis Diskriminan - Azzah Nazhifa Wina Ramadhani; Aulia Ramadhanti; Aini Divayanti Arrofah; M. Nabil Saputra; Dita Amelia; M. Fariz Fadillah Mardianto; Elly Ana (Jurnal Matematika, Statistika dan Komputasi, 2024)
One of the key achievements in national development is the success in building villages as the smallest administrative units because that is starting point for the development of an economy within the community. Therefore, it is crucial for the government to conduct mapping for development to enhance the quality of the population and the respective regions. The purpose of this research is to categorize several districts in Province of Bali into specific statues based on Village Development Index using discriminant analysis method. The result of this research indicates a high classification rate of 92.857% for the discriminant model formed. This suggests that almost all districts in both categories have been classified into groups that align with the original data.